Implementing Lean management in healthcare to improve patient outcomes - Abdullah Hamed Althagafi,; Ahmad Mohmmad Alharthi,; Abdalrhman Ali Alahmed,; Mohannad Ali Sait,; Mohammed Taher Shawk,; Hattan Mohamed Makkawi,; Faris Faisal Alshaikh, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The escalating pressures on the healthcare system necessitate innovative strategies that enhance operational efficiency while improving patient outcomes and satisfaction. Lean management, originally developed in manufacturing, has emerged as a transformative approach within healthcare, prioritizing the elimination of waste and the maximization of value from the patient's perspective. This paper examines the application of Lean principles in healthcare settings, discussing core concepts such as value identification, value stream mapping, continuous improvement, staff empowerment, and respect for people. Through an exploration of successful case studies, including Virginia Mason Medical Center and ThedaCare, the article illustrates the tangible benefits of Lean implementation, such as reduced patient wait times, improved care quality, and increased staff engagement. Additionally, essential strategies for effective Lean implementation are outlined, emphasizing the importance of leadership commitment, staff involvement, ongoing education, cultural integration, and performance measurement. By adopting Lean management, healthcare organizations can foster a culture of continuous improvement that not only enhances operational efficiencies but also significantly contributes to improved patient care and outcomes in an increasingly complex healthcare landscape.